2023
DOI: 10.22271/kheljournal.2023.v10.i1b.2757
|View full text |Cite
|
Sign up to set email alerts
|

The major aspects determining the most prevalent injuries in baseball: A review

Abstract: The major intention of this study is to identify the major injuries that related to the baseball players. Twenty-seven articles related with common baseball injuries in game situation, player position, training period were used for this study. The most common upper body injuries are happened shoulder, head, hand, and lower body injuries are occurred in the knee, ankle, and upper leg. The pitchers are common with upper body injuries and knee and collision injuries are common with defensive players including cat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Kabaddi, an aggressive sport originating from India, poses a significant risk of knee injury to its players, with studies highlighting the prevalence of such injuries (Dahiya & Kumar, 2023;Mondal, 2017). Research into the profile of knee injuries among elite Iranian karateka also revealed a high incidence of knee injuries, particularly involving the anterior cruciate ligament (ACL), articular cartilage and meniscus (Naserpour et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Kabaddi, an aggressive sport originating from India, poses a significant risk of knee injury to its players, with studies highlighting the prevalence of such injuries (Dahiya & Kumar, 2023;Mondal, 2017). Research into the profile of knee injuries among elite Iranian karateka also revealed a high incidence of knee injuries, particularly involving the anterior cruciate ligament (ACL), articular cartilage and meniscus (Naserpour et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Ankle injuries are a common concern in Kabaddi, with research highlighting their frequency and impact on A h e a d o f P r i n t players. Research shows that knee injuries are common in Kabaddi players, followed by ankle injuries, emphasizing the vulnerability of the lower extremities in this sport (Dahiya & Kumar, 2023;Mondal, 2017;Pal et al, 2021). Ankle ligament OEO is particularly important, with varying percentages reported across different age groups and genders of Kabaddi players, demonstrating the importance of these injuries across different demographics.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations